Determinants of Tetanus Toxoid (TT) Coverage in Premarital: Systematic Review - Dewi Puspitaningrum; Muhammad Zen Rahfiludin (Gaster, 2022)
Background: Many health programs have been launched by the government in reducing maternal and infant mortality. It should be re-examined that the health program will be successful if something is done that is preventive in nature and something very urgent needs to be considered, namely the decreased coverage of TT immunization in premarital. TT immunization before pregnancy really needs to be considered, which is one of the preventions before premarital couples enter the reproductive stage. This prevention program needs to be considered for the continuation of further reproductive health. The purpose of this study is to identify the determinant factors that affect the decline in TT immunization coverage in premarital.Method: the method used is a systematic review through the study of national online data studies through Google Scholar, Garuda Portal and international online data from Pubmed, Science Direct and Proquest from 2012-2021 with Keywords: TT immunization in women of childbearing age, preconception women, and premarital couples which is then carried out is selected based on the inclusion criteria and exclusion criteria, then an analysis is carried out on the team systematically and team discussions to facilitate understanding of the determinants of premarital tetanus toxoid immunization coverage.Results: Based on studies that have determined the coverage of TT immunization in the premarital, there are 3 aspects that need to be considered, namely (1) premarital perception of TT immunization, (2) policies in providing TT immunization in premarital and (3) screening in premarital examination.Conclusion: Found factors that influence from several studies, namely education, knowledge, health services, social economy, health insurance services, ease of information, premarital screening programs as a determinant of the existence of TT immunization coverage in premarital.